A current perspective on treatment of adrenocortical carcinoma. (September 2014) - Terzolo, Massimo; De Francia, Silvia; Ardito, Arianna; Perotti, Paola; Ferrari, Laura; Berruti, Alfredo
Abstract : Introduction: Adrenocortical carcinoma (ACC) is an aggressive tumor with a short life expectancy and severe impact on quality of life. Due to the rarity of ACC progress in the development of treatment options beyond surgery has been limited. Areas covered: Postoperative treatment with mitotane for adjuvant purposes is currently recommended in many expert centers for patients at elevated risk of recurrence. Lacking data from prospective trials, evidence in favor of adjuvant mitotane comes from retrospective studies that have shown a benefit in recurrence-free survival in treated patients. The management of patients with recurrent and metastatic disease is challenging and the prognosis is often poor. Mitotane monotherapy may be used in patients with a low tumor burden and/or less aggressive disease, while cytotoxic chemotherapy is the treatment of choice for progressing tumors. No effective target therapy emerged from preclinical studies. Expert opinion: At our center, adjuvant mitotane treatment is recommended in all patients bearing ACC at high risk of recurrence. Patients with low-risk tumors are encouraged to enter the ADIUVO trial. A monitored mitotane approach is used trying to reach and maintain a mitotane level of 14 – 20 mg/l. For treatment of advanced ACC, patients are stratified according to their prognostic factors and consequently apply mitotane or mitotane plus etoposide, doxorubicin and cisplatin. In a number of patients, who are elderly or present with impaired clinical conditions, a simplified scheme with mitotane and cisplatin was chosen.